Predictors of postoperative hospital length of stay after total knee arthroplasty - Davide Tornese; Alessandro Robustelli; Gabriele Ricci; Paola Maria Vittoria Rancoita; Nicola Maffulli; Giuseppe Michele Peretti (Singapore Medical Journal)
Introduction: We aimed to collect and analyse clinical and functional variables of patients undergoing rehabilitation after total knee arthroplasty (TKA), to identify the variables that influence the postoperative hospital length of stay (LOS). Methods: We conducted a retrospective analysis of prospectively collected data of 1,082 consecutive patients (746 females and 336 males) who underwent primary TKA and rehabilitation in our orthopaedic institute between January 2013 and July 2017. Clinical and anthropometric data were analysed using a multivariate linear regression model. Results: The average LOS was 5.08 ± 2.52 days in the Department of Orthopaedic Surgery and 12.67 ± 5.54 days in the Sports Rehabilitation Unit. Factors such as age, female sex and the presence of comorbidities were predictive of a longer stay. The presence of caregiver assistance at home was associated with shorter LOS. There was no evidence of a statistically significant positive association between body mass index and LOS. Conclusion: An in-depth and early knowledge of factors that influence LOS may enable the multidisciplinary team to plan a patient-tailored rehabilitation path and better allocate resources to maximise patients’ functional recovery, while reducing LOS and the overall cost of the procedure.